KARAKTERISASI KULTUR MAKROFAG HASIL ISOLASI Mouse Peritoneum Makrofag (MPM) - Susanti, Erna (El-Hayah : Jurnal Biologi, 2015)
The aims of this study is to determine the MPM isolation techniques, results of the isolation and identification, so it can be used as a reference for the studies using macrophage cell cultures. The most appropriate source for culturing macrophages are the primary culture of MPM. Resident peritoneal macrophages (RPM) is a free-living phagocytic cells in the peritoneal cavity. Millions of resident macrophages can be taken from the mice. The peritoneal cavity is an easy place to harvest the resident macrophages. Identification of macrophages was conducted using flowcytometry with specific marker CD 11B. While the morphology of macrophages in culture was observed microscopically The results of the study showed the average number of macrophages 1.03 x 106 cells / ml were isolated from peritoneal cavity of mice. The result of identification with flowcytometry with marker CD 11 B shows positive results macrophages. While the observation of morphological characteristics of macrophages cultures show the same characteristics as the result of research conducted by Kim in 1997 and Wang et al, 2010 so that it can be concluded that macrophages can be isolated from the peritoneal cavity and can be used as a source of primary cultures of macrophages with good results and can be applied to studies related to the function and activation of macrophages in vitro. Keyword; Kultur Makrofag, Isolasi Mouse Peritoneum Makrofag (Mpm)